2014
DOI: 10.1159/000360538
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome after the Treatment of Loop Electrosurgical Excision Procedure or Cold-Knife Conization for Cervical Intraepithelial Neoplasia

Abstract: Objective: The aim of this study was to investigate the influence on fertility and pregnancy outcome in cervical intraepithelial neoplasia (CIN) patients after a loop electrosurgical excision procedure (LEEP) or cold-knife conization (CKC). Methods: 269 patients with CIN-II-III who wanted to conceive were prospectively enrolled in this randomized clinical trial to receive either the LEEP or CKC procedure. Fertility, neonatal and maternal outcomes were observed and compared. Results: 244 evaluable patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…Our study found that a prior cervical excision procedure was associated with an increased risk of forceps delivery(p = 0.034), and the main purpose of forceps delivery was to shorten the second stage of labor(p = 0.033). The cervix, which is consisted of smooth muscle, broblasts, epithelium, and blood vessels, is considered to play an important role in delivery [15,16]. Theoretically, cervical excision procedure has an impact on the structure and function of the uterus, which may affect the process of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that a prior cervical excision procedure was associated with an increased risk of forceps delivery(p = 0.034), and the main purpose of forceps delivery was to shorten the second stage of labor(p = 0.033). The cervix, which is consisted of smooth muscle, broblasts, epithelium, and blood vessels, is considered to play an important role in delivery [15,16]. Theoretically, cervical excision procedure has an impact on the structure and function of the uterus, which may affect the process of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previously reported cases, primary DLBCL of the female genital tract can occur at any age. With the introduction of immunochemotherapy, we could hope for a promising result regarding disease-free survival, but this introduces another important challenge - how to preserve the childbearing potential [1,18,19]. There are only limited data on the recommended time of contraception, the risk of miscarriages or the pregnancy outcome of women with and after R-CHOP immunochemotherapy in primary NHL of the female genital tract [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive cervical cancer is the second most common cancer in women, with an estimated 529,000 new cases and 274,000 deaths each year [1,2]. It is a serious threat to women's quality of health and life.…”
Section: Introductionmentioning
confidence: 99%